Factors Related to Anemia in Trimester of III among Pregnant Women in the Working Area of Puskesmas, Cengkareng District, 2019 - Ummu Nida; Gisely Vionalita (International Journal of Nursing and Health Services (IJNHS), 2021)
Anemia in pregnant women is a condition of red blood cells (erythrocytes) <11 gr/dl in trimesters III. It is unable to fulfill its function as a carrier of oxygen to all body tissues. Data obtained from the Cengkareng District Health Center recorded the number of anemia sufferers in third-trimester pregnant women in October 2019 as many as 40 people. This study aims to determine the factors associated with anemia incidence in third-trimester pregnant women in the Cengkareg District Health Center in 2019. This type of research is quantitative with a case-control research design to obtain field data of 80 respondents conducted by filling in medical records with total sampling techniques for case group respondents and control groups. The results of the Chi-Square test showed a relationship between nutritional status (p = 0.002), ANC visits (p = 0,000), parity (p = 0.022) and the incidence of anemia in third trimester pregnant women. It is expected that the public health center can further optimize programs for pregnant women so that they do not experience an increase in third-trimester pregnant women's anemia